A Review of the Utility of Established Cell Lines for Isolation and Propagation of the Southern African Territories Serotypes of Foot-and-Mouth Disease Virus - Kitsiso Gaboiphiwe; Tshephang Iris Kabelo; Petronella Thato Mosholombe; Joseph Hyera; Elliot Mpolokang Fana; Kabo Masisi; Kebaneilwe Lebani (Viruses)
Cell culture underpins virus isolation and virus neutralisation tests, which are both gold-standard diagnostic methods for foot-and-mouth disease (FMD). Cell culture is also crucial for the propagation of inactivated foot-and-mouth disease virus (FMDV) vaccines. Both primary cells and cell lines are utilised in FMDV isolation and propagation. Widely used cell lines for FMDV and isolation and propagation include baby hamster kidney cells (BHK-21), swine kidney cells (IB-RS-2), foetal goat tongue (ZZ-R 127), foetal porcine kidney cells (LFBKvB6), bovine kidney cells (BK), human telomerase reverse transcriptase bovine thyroid (hTERT-BTY) and porcine kidney-originating PK-15 or SK 6 cell lines. This review highlights how different receptors and molecules—integrins, heparan sulphate (HS), and the Jumonji C-domain containing Protein 6 (JMJD6)—found on the surface of different cell types contribute to differences experienced with susceptibility and sensitivity of the cells to infection with different serotypes of FMDV. This review specifically focuses on Southern African territory (SAT) serotypes, which are unique to the Southern African context and are often under-investigated in cell line development for FMDV isolation and propagation.